Investigation of Pre-lithiation in Graphite and Hard-Carbon Anodes Using Different Lithium Source Structures. Issue 14 (1st January 2017) - Shellikeri, A.; Watson, V.; Adams, D.; Kalu, E. E.; Read, J. A.; Jow, T. R.; Zheng, J. S.; Zheng, J. P.
Abstract : Energy storage devices like batteries and supercapacitors, have become indispensable in portable devices and electric vehicles. But, the carbon anodes used in these devices, exhibit a significant loss in their initial capacity (graphite: 6.6% and hard carbon: 29.8%) due to the consumption of Li ions from electrolyte during solid electrolyte interface layer formation and other non-reversible reactions, and if unaddressed, can potentially diminish this advantage. Pre-lithiation treatment of carbon anodes can mitigate this loss, apart from improving the cell working potential, hence enhancing cell energy density and cyclability. We investigate in this report a direct-contact lithiation process in graphite and hard carbon anodes using four distinct lithium source structures. The results show that the type of Li-source structure employed for anode pre-lithiation can have a major impact on the electrode physical properties, pre-lithiation times and the pre-lithiation anode potentials achieved, potentially effecting the SEI properties, cycle life, and the electrode processing costs.